Use the chain rule with Fundamental Theorem of calculus

g′(x)=f(h(x)) h′(x) − f(ϕ(x)) ϕ′(x)

=f(x²) × d/dx (x²) − f(5x+1) × d/dx (5x+1)

= (sin x²)/(x²) × (2x) - (sin (5x+1))/(5x+1) × 5

= (2x sin x²)/(x²) - (-5 sin (5x+1))/(5x+1)

Use the chain rule with Fundamental Theorem of calculus

g′(x)=f(h(x)) h′(x) − f(ϕ(x)) ϕ′(x)

=f(x²) × d/dx (x²) − f(5x+1) × d/dx (5x+1)

= (sin x²)/(x²) × (2x) - (sin (5x+1))/(5x+1) × 5

= (2x sin x²)/(x²) - (-5 sin (5x+1))/(5x+1)

Didn't find the answer you were looking for?